Time-Resolved Fluorescence and Anisotropy-Sensitive 1,2-Dimyristoyl-Sn-Glycero-3-(7-Aminocoumarin) Phosphoetanolamide Probe for Studying Membrane Lipid Domains - Aspee-Lamas, A; Zúñiga-Núñez, D; Mura-Mardones, F (Elsevier Ltd, 2023)
A fluorescent probe C-DMPE was synthesised to monitor interfacial membrane properties by conjugating coumarin-343 and 1,2-dimyristoyl-sn-glycero-3-phosphorylethanolamine (DMPE), anchoring the 7-aminocoumarin moiety close to the phospholipid polar head at the membrane interface. Large unilamellar vesicles (LUV) of 1,2-dipalmitoyl-sn-glycero-3-phosphatidylcholine (DPPC), of 1,2-dioleyl-sn-glycero-3-phosphatidylcholine (DOPC) and cholesterol were employed as a model of lipid bilayer. Time-resolved fluorescence developed an emissive Internal Charge Transfer excited state with a long fluorescence lifetime (τ1), a Locally Excited state with an intermediate fluorescence lifetime (τ2), and a short lifetime (τ3) associated with an intermolecular quenching by interaction with a phosphate group of neighbour phospholipids, as is clearly shown by molecular dynamics simulations. Shorter values of fluorescence lifetimes τ1 and τ3 were observed in DOPC with respect to DPPC, responding to a more fluid membrane with more significant water accessibility in DOPC than DPPC. However, in DPPC:DOPC vesicles, these fluorescence lifetimes are even shorter, allowing to be attributed to favourable sensing of boundary limit lipid domains. In similitude, time-resolved anisotropy showed shorter rotational correlation times φ1, in DPPC: DOPC vesicles than in DOPC associated with a faster internal rotational movement of the 7-aminocoumarin group in domains than in fluid a DOPC membrane. In addition, shorter rotational correlation times, φ2, were also observed in DPPC:DOPC vesicles compared to DPPC, suggesting a faster lateral diffusion of the probe in the presence of domains. © 2023 Elsevier Ltd